2015
DOI: 10.1080/09638199.2014.1001772
|View full text |Cite
|
Sign up to set email alerts
|

Financial liberalization and remittances: Recent panel evidence

Abstract: We investigate the impact of financial liberalization on remittances to 84 countries over the period 1986-2005. Explicitly accounting for the multidimensionality of financial reform, we find that the various dimensions impact remittances differently: Increased economic freedom in the financial sector, as captured by absence of direct government control over the allocation of credit, has a positive and immediate impact. However, the improved robustness of financial markets, as captured by the development of sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 62 publications
(70 reference statements)
3
14
0
Order By: Relevance
“…According to the obtained results, country risk encourages money sent home. This is in line with Bang et al (2013) and Lartey (2016) results but it is in contrast with the results of Singh (2012) who found that SSA countries with better and stable political systems would receive more remittances. However, Bettin, Lucchetti, and Zazzaro (2009) showed that the composite risk index has no effects on remittances.…”
Section: Determinants Of Remittancessupporting
confidence: 85%
See 1 more Smart Citation
“…According to the obtained results, country risk encourages money sent home. This is in line with Bang et al (2013) and Lartey (2016) results but it is in contrast with the results of Singh (2012) who found that SSA countries with better and stable political systems would receive more remittances. However, Bettin, Lucchetti, and Zazzaro (2009) showed that the composite risk index has no effects on remittances.…”
Section: Determinants Of Remittancessupporting
confidence: 85%
“…Few studies have found a positive risk effect on remittances as evidence for altruism. In this case, remittances are sent to support families left behind (Bang, Mitra, & Wunnava, 2013). Lartey (2016) found that remittances have a negative relationship with institutional quality, which would not be consistent with the hypothesis that remittances are sent for investment purposes.…”
Section: Literature Review: Determinants Of Workers’ Remittances and mentioning
confidence: 99%
“…For this reason, low cost diets are associated with higher calorie intake at the expense of fewer nutrients [ 6 ], while healthier diets tend to be more expensive [ 11 , 12 , 13 , 14 ]. Additionally, the price of food has been found to be associated with blood cholesterol levels [ 15 ], blood glucose levels [ 16 ], and obesity [ 17 ]. While prior work has shown that higher quality diets cost more than poorer quality diets, there is little evidence examining the association between local food prices across multiple regions and overall diet quality.…”
Section: Introductionmentioning
confidence: 99%
“…for Pakistan;Abiad et al (2010) for 91 economies of the world;Bang et al (2013) andKeshri and Bhagat (2013) for India; Akkoyunlu and Siliverstovs (2013) for Turkey; andImai et al (2014) for Asian economies. However, none of the studies investigates the impact of remittances on money demand.…”
mentioning
confidence: 99%